Stock Return Synchronicity and Analysts’ Forecast Properties - Cho, Joong-Seok; Park, Hyung Ju; Park, Ji-Hye (Gadjah Mada International Journal of Business, 2016)
Using stock return synchronicity as a measure of a firm’s information environment, our research investigates how the firms’ stock return synchronicity affects analysts’ forecast properties for the accuracy and optimism of the analysts’ annual earnings forecasts. Stock return synchronicity represents the degree to which market and industry information explains firm-level stock return variations. A higher stock return synchronicity indicates the higher quality of a firm’s information environment, because a firm’s stock price reflects more market-level and industry-level information relative to firm-specific information. Our study shows that stock return synchronicity positively affects the forecast properties. Our finding shows that when stock return synchronicity is high, analysts’ annual earnings forecasts are more accurate and less optimistically biased.